Recent advances in dual-carbon based electrochemical energy storage devices. (June 2020) - Hou, Ruilin; Liu, Bao; Sun, Yinglun; Liu, Lingyang; Meng, Jianing; Levi, Mikhael D.; Ji, Hengxing; Yan, Xingbin
Abstract: Dual-carbon based rechargeable batteries and supercapacitors are promising electrochemical energy storage devices because their characteristics of good safety, low cost and environmental friendliness. Herein, we extend the concept of dual-carbon devices to the energy storage devices using carbon materials as active materials in both anode and cathode, and offer a real-time and overall review of the representative research progress concerning such generalized dual-carbon devices. In this review, the charge storage mechanisms of various ions on different carbonaceous electrodes are introduced at first. Then, the research progress and problems of dual-carbon devices based on four types of charge-storage mechanisms including "adsorption-adsorption", "adsorption-intercalation", "intercalation-adsorption" and "intercalation-intercalation" are systematically discussed. Finally, prospects for future research directions and challenges of the dual-carbon devices are presented, and some new insights are proposed as well. Graphical abstract: Image 1 Highlights: Defined the generalized dual-carbon devices and classify the dual-carbon devices for the first time. Summarize the ion-storage mechanisms on carbonaceous electrodes of dual-carbon devices. Overview the research progress, advantages, problems and solutions of various dual-carbon devices. Propose new insights for the future research directions and challenges of the dual-carbon devices.